Increased risk of catheter colonization and catheter-related infections in severe immunocompromized patients with multiple myeloma undergoing high-dose glucocorticoid treatment - Goldschmidt, Hartmut; Salwender, Hans; Hahn, Uwe; Hegenbart, Ute; Egerer, Gerlinde; Wallmeier, Martin; Jansen, Bernd; Haas, Rainer (Zentralblatt für Bakteriologie, 1998)
Catheter-related infections (CRI) are an important problem in medicine because of major consequences for treatment, prolongation of hospitalization and increasing therapy costs. Malignancies, immunodeficiency, severe burns and malnutrition compromise host defense. Studies to quantify the increased risk of CRI in immunocompromised patients are required. We analyzed the influence of immunoglobulin deficiency and high-dose glucocorticoid treatment in patients with multiple myeloma with regard to catheter colonization and CRI. In patients with multiple myeloma, central venous catheters (CVC) were significantly more frequently colonized (>15 CFU) as compared to patients with other malignancies undergoing chemotherapy. We found a tendency towards a higher CRI rate in the myeloma patient group. Interestingly, despite of the significantly higher incidence of catheter colonization and a tendency towards higher CRI rates in severely immuno-compromised patients, the incidence of signs of local (redness of the entry site) and systemic (fever) host reactions is reduced in myeloma patients. To decrease the CRI rate in myeloma patients during chemotherapy which includes high-dose glucocorticoids, we use antibacterial (silver-coated) catheters.